2011
DOI: 10.1089/scd.2011.0279
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia-Induced Neural Stem/Progenitor Cells in the Pia Mater Following Cortical Infarction

Abstract: Increasing evidence shows that neural stem/progenitor cells (NSPCs) can be activated in the nonconventional neurogenic zones such as the cortex following ischemic stroke. However, the precise origin, identity, and subtypes of the ischemia-induced NSPCs (iNSPCs), which can contribute to cortical neurogenesis, is currently still unclear. In our present study, using an adult mouse cortical infarction model, we found that the leptomeninges (pia mater), which is widely distributed within and closely associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

20
225
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(247 citation statements)
references
References 64 publications
20
225
2
Order By: Relevance
“…Activated pericytes have been shown to detach from local capillaries, migrate to the site of injury and differentiate into myofibroblasts (Goritz et al, 2011;Lin et al, 2011;Ren et al, 2013). However, the recruitment of pericytes following injury and their collagen-producing capacity may be dependent on both the type of injury and the tissue under investigation (Birbrair et al, 2014a;Nakagomi et al, 2011). Activated pericytes have been shown to upregulate genes associated with migration, for example ADAMTS1 and TIMP3 (Hung et al, 2013;Schrimpf et al, 2012).…”
Section: Mechanisms Of Msc and Pericyte Recruitment To Sites Of Injurymentioning
confidence: 99%
“…Activated pericytes have been shown to detach from local capillaries, migrate to the site of injury and differentiate into myofibroblasts (Goritz et al, 2011;Lin et al, 2011;Ren et al, 2013). However, the recruitment of pericytes following injury and their collagen-producing capacity may be dependent on both the type of injury and the tissue under investigation (Birbrair et al, 2014a;Nakagomi et al, 2011). Activated pericytes have been shown to upregulate genes associated with migration, for example ADAMTS1 and TIMP3 (Hung et al, 2013;Schrimpf et al, 2012).…”
Section: Mechanisms Of Msc and Pericyte Recruitment To Sites Of Injurymentioning
confidence: 99%
“…The leptomeninges are histologically continuous with the cortical parenchyma along the blood vessels and are located at a perivascular niche as vascular pericytes (7). We showed that leptomeningeal nestin + cells spread into the cortical parenchyma, localized near CD31 + endothelial cells, and expressed pericytic makers such as PDGFRβ and NG2 (5). Although the functions of pericytes remain unclear, it has been well-documented that pericytes in various organs, including the CNS, have multipotent stem cell activity (8).…”
mentioning
confidence: 85%
“…These findings showed that leptomeningeal NSPCs have potential to contribute to cortical neurogenesis during early developmental stages. Using adult mice following ischemic stroke, we previously showed that nestin + ischemia-induced NSPCs (iNSPCs) were present in the leptomeninges of ischemic areas, and they were not observed in the leptomeninges of nonischemic areas (5). Leptomeningeal cells isolated from ischemic areas produce neurosphere-like cell clusters that give rise to neural cells, including neurons (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Meninges in the brain and spinal cord may also directly harbor stem cells under basal conditions (8) and in response to insults, such as stroke and spinal cord injury (9,10). Thus, the meninges regulate the development of the brain and may also harbor stem cells in adult brain.…”
mentioning
confidence: 99%